Post-race reactions: The emotional paradox of high performance and anxiety - a conventional content analysis - Augustsson, S. R.; Bergh, M.; Petersson, K. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Studies examining post-race emotional experiences in the context of endurance races among recreational athletes are scarce. The purpose of this study was to describe how recreational athletes experience the time after completing an endurance race.